Reaction of diaryl-1,2-diones with triphenylphosphine and diethyl azodicarboxylate leading to N, N-dicarboethoxy monohydrazones via a novel rearrangement - Nair, Vijay; Biju, Akkattu T.; Abhilash, K. G.; Menon, Rajeev S.; Eringathodi, Suresh (Organic Letters, 2005)
A mechanistically novel reaction of diaryl-1,2-diones with diethyl azodicarboxylate and triphenylphosphine to afford N,N-dicarboethoxy monohydrazones is described. The reaction proceeds via a nitrogen to nitrogen migration of a carboethoxy group.

DMAP-catalyzed reaction of beta-ketoesters and dimethyl acetylenedicarboxylate: an efficient synthesis of polysubstituted benzenes and biaryls - Nair, Vijay; Vidya, N.; Biju, Akkattu T.; Deepthi, Ani B.; Abhilash, K. G.; Eringathodi, Suresh (Tetrahedron, 2006)
A DMAP catalyzed tandem addition–cyclization–dehydration sequence involving dimethyl acetylenedicarboxylate and β-ketoesters leading to polysubstituted benzene/biaryl derivatives is presented.

1,2-Benzoquinones in Diels-Alder reactions, dipolar cycloadditions, nucleophilic additions, multicomponent reactions and more - Nair, Vijay; Menon, Rajeev S.; Biju, Akkattu T.; Abhilash, K. G. (Chemical Society Reviews, 2012)
A brief account of the recent developments in the chemistry of 1,2-benzoquinones is presented in this tutorial review. The title compounds exhibit commendable versatility in both Diels-Alder and dipolar cycloaddition reactions. They have also been employed as electrophilic reaction partners in nucleophile-triggered catalytic processes and related multicomponent reactions. These, along with other reactions described here, lead to the synthesis of densely functionalised carbocyclic and heterocyclic frameworks that are otherwise difficult to access.